ОЮУНЫ САН ХӨМРӨГТ КАЗАХ ЭМЭГТЭЙЧҮҮДИЙН ОРУУЛСАН ХУВЬ НЭМЭР - Б.Алтангүл (Politology, 2023)
Kazakh women’s contribution to the intellectual property of the culture. Women of an every country of the world make their own contribution to the development of a family, a policy, a society and a country as well. A non-governmental organization (NGO) "Arular" or "Women" since it’s time of foundation pays much attention to the study and research of Kazakh people’s life who have moved to Mongolia for residential living upon a time and especially to the role of Kazakh women in a society. Kazakh women on one hand are a "pillar" of a family head, a mother who takes care of children, a bridge of a family, a daughter who takes care of parents, a reliable protector of a family and an advisor to a friend but on the other hand so far from generation to generation they try their utmost to make their own contribution to the development of a society as well. We can see from the historical documents that Kazakh women after a victory of the Revolution in Mongolia went side by side with men and made their contribution to the deal of development and prosperity of the country and paid a great attention to the deal of passing down to the next generations their knowledge and experience. Our goal is to show up mainly how do they reach success in the intellectual field as well.